Systematic review and meta-analysis of Jueyin disease theory in the treatment of gangrene with traditional Chinese medicine formulations - Youzhi Zhang; Bochuan Lv; Yue Teng; Jintao Xu (Systematic Reviews)
Abstract Objective This review aims to systematically evaluate the application of Jueyin disease theory in the diagnosis and treatment of gangrene within the framework of traditional Chinese medicine (TCM). Through systematic review and meta-analysis, the efficacy of commonly used TCM formulations, including Wumei pill, Pulsatilla decoction, and Dang-Gui-Si-Ni decoction, is explored. Methods A systematic search of PubMed, Web of Science, and CNKI was conducted, integrating meta-analysis and systematic review. Clinical trials and case reports based on Jueyin disease theory for gangrene treatment were included. Data extraction, quality assessment, and statistical analyses were performed. Results A total of nine studies met the inclusion criteria. The meta-analysis indicated that TCM formulations significantly improved clinical outcomes, particularly in enhancing the ankle-brachial index (ABI) and maximum walking distance, with mean differences of 0.17 (95% CI, 0.11, 0.24; p < 0.01) and 293.22 (95% CI, 174.85, 411.60; p < 0.01), respectively. Sensitivity analysis and tests for publication bias confirmed the robustness and consistency of the findings. Sensitivity analysis and publication bias assessment confirmed the robustness and reliability of the results. Conclusion Jueyin disease theory and its related formulas (Wumei pill, Pulsatilla decoction, and Dang-Gui-Si-Ni decoction) demonstrate significant clinical value in traditional Chinese medicine (TCM) treatment of gangrene, effectively improving clinical symptoms and blood circulation. The findings provide scientific evidence for the modern application of Jueyin disease theory in TCM while acknowledging limitations such as small sample sizes and study heterogeneity, offering valuable insights for future research and clinical practice.